2006
DOI: 10.1158/1078-0432.ccr-05-1766
|View full text |Cite
|
Sign up to set email alerts
|

Expression of targeting protein for xklp2 associated with both malignant transformation of respiratory epithelium and progression of squamous cell lung cancer.

Abstract: Purpose: Expression of targeting protein for Xklp2 (TPX2), a microtubule-associated protein, is tightly cell cycle regulated. Abnormally expressed TPX2 has been reported in various malignancies, but less is known in lung cancer. The present study appraised the significance of TPX2 aberrant expression for tumorigenesis and progression of human squamous cell carcinoma (SCC) in lung. Experimental Design and Results: The expressive status of TPX2 was firstly examined with lung cancer (L, PAa, and PG) and immortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 24 publications
3
65
0
Order By: Relevance
“…TPX2 is a cell cycle-associated protein and plays a significant role in the microtubule formation at kinetochores (5), although its overexpression induces monopolar spindle structures in Xenopus egg extracts (25). Overexpression of TPX2 has been reported in several human cancers (22). In the present study, we found that the expression level of TPX2 mRNA was significantly increased in oral SCCs compared with normal gingivae.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…TPX2 is a cell cycle-associated protein and plays a significant role in the microtubule formation at kinetochores (5), although its overexpression induces monopolar spindle structures in Xenopus egg extracts (25). Overexpression of TPX2 has been reported in several human cancers (22). In the present study, we found that the expression level of TPX2 mRNA was significantly increased in oral SCCs compared with normal gingivae.…”
Section: Discussionsupporting
confidence: 56%
“…The reaction mixture contained 1.0 μg of cDNA, 10 μl of SYBR-Green PCR master mix (Toyobo, Tokyo, Japan) and 10 pmol of each pair of oligonucleotide primers. Previously published primer sequences were used for RHAMM and TPX2 (12,22). The primer sequences were: RHAMM; 5'-CAGGTCACCCAAA GGAGTCTCG-3' (sense), 5'-CAAGCTCATCCAGTGTT TGC-3' (antisense) (537 bp PCR products), TPX2; 5'-ACCT TGCCCTACTAAGATT-3' (sense), 5'-AATGTGGCACAG GTTGAGC-3' (antisense) (176 bp PCR products), and G3PDH; 5'-ACCACAGTCCATGCCATCAC-3' (sense), 5'-TCCACCACCCTGTGGCTGTA-3' (antisense).…”
Section: Methodsmentioning
confidence: 99%
“…Polo-like kinase 1, MAPK, and Cdc2) are not affected is important for the following reasons. First, both Aurora A and TPX2 (initially identified as REPP86 (restrictedly expressed proliferation-associated protein of 86 kDa) are overexpressed in some tumors (61)(62)(63). Furthermore, knockdown of TPX2 significantly reduces the survival of multiple human cancer cell lines (64).…”
Section: Discussionmentioning
confidence: 99%
“…30,41,42 Introduction of non-degradable mutant of NuSAP, TPX2 or Aurora B into cells resulted in disordered mitosis caused by abnormal spindle structure and/or promote anchorage-independent growth, similar to the phenotypes of these factors overexpressed in cancer tissues. 43,44 These findings strongly suggest that Cdh1-mediated degradation of mitotic spindle regulators is crucial for proper cell cycle progression. Thus, further identification of a non-degradable mutant of TACC3 should help to elucidate the regulatory event of Cdh1 on TACC3 in cell cycle progression.…”
Section: Cdh1 Promotes Tacc3 Ubiquitination In Cellsmentioning
confidence: 92%